2013
DOI: 10.1016/j.nbd.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The 70 kDa heat shock protein protects against experimental traumatic brain injury

Abstract: Traumatic brain injury (TBI) causes disruption of the blood brain barrier (BBB) leading to hemorrhage which can complicate an already catastrophic illness. Matrix metalloproteinases (MMPs) involved in the breakdown of the extracellular matrix may lead to brain hemorrhage. We explore the contribution of the 70 kD heat shock protein (Hsp70) to outcome and brain hemorrhage in a model of TBI. Male, wildtype (Wt), Hsp70 knockout (Ko) and transgenic (Tg) mice were subjected to TBI using controlled cortical impact (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 57 publications
3
39
0
1
Order By: Relevance
“…Hsp70 has an anti-inflammatory role in brain ischemia [43]. Previously, Hsp70 expression was shown to be increased following controlled cortical impact in a TBI mouse model, and it has a protective role in experimental TBI [44]. Here, we also found that Hsp70 gene expression was increased.…”
Section: Discussionsupporting
confidence: 68%
“…Hsp70 has an anti-inflammatory role in brain ischemia [43]. Previously, Hsp70 expression was shown to be increased following controlled cortical impact in a TBI mouse model, and it has a protective role in experimental TBI [44]. Here, we also found that Hsp70 gene expression was increased.…”
Section: Discussionsupporting
confidence: 68%
“…Infiltration of inflammatory cells can lead to activation of microglia and astrocytes and persists for hours to days. Inflammation in ischemic tissues exacerbates tissue damage leading to worse neurological outcomes (58). The inflammatory changes also occur in ischemic myocardium and peripheral vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…(Inducible) Hsp70 has long been associated with protective effects in experimental models of traumatic brain injury, stroke and other organ injuries [37][38][39]. Likewise, clinical studies have begun to elucidate the association between Hsp70 and outcome in trauma and sepsis [40][41][42].…”
Section: Accepted Manuscriptmentioning
confidence: 99%